Issues and Challenges in Cataloguing Arabic Books in Malaysian Academic Libraries - Ismail, Mohd Ikhwan; Md. Roni, Nurul Azurah (2011)
Education in Library and Information Science is a requirement to become a librarian. There are a lot of syllabuses and subjects to concentrate on such as cataloguing and classification, information retrieval, knowledge management, and reference. Library as a centre of information has been developing year by year with various types of collections written and presented in many languages such as English, Arabic and Malay. The different languages come with different letters, words, pronunciations and characters. They can bring problems and challenges in cataloguing process including determining the access points, subject headings and call number. The objective of this study is to identify the challenges in cataloguing Arabic books for cataloguers in Malaysian academic libraries.